Reform of ill-health retirement of police in England and Wales: Impact on pension liabilities and the role of local finance - Rowena Crawford; Richard Disney (Institute for Fiscal Studies (IFS), 2013)
We examine ill-health retirement of police officers in England and Wales between 2002-3 and 2009-10. Differences in ill-health retirement rates across forces are statistically related to area-specific stresses of policing and force-specific differences in human resources policies. Reforms to police pensions plans- in particular a shift in the incidence of financing ill-health retirement from central government to local police authorities- impacted on the level of ill-health retirement, especially among forces with above-average rates of retirement. We find that residual differences in post-2006 ill-health retirement rates across forces are related to their differential capacities to raise revenue from local property taxes. We quantify the impact of these reforms on overal pension plan liabilities.
Keywords: H75; J26; J45; 330; police pensions; ill-health retirement; state and local finance